Water exchange in lanthanide complexes for MRI applications. Lessons learned over the last 25 years. Issue 30 (26th June 2019) - Caravan, Peter; Esteban-Gómez, David; Rodríguez-Rodríguez, Aurora; Platas-Iglesias, Carlos
Abstract : Coordination chemistry offers convenient strategies to modulate the exchange of coordinated water molecules in lanthanide-based contrast agents. Abstract : The water exchange rates of water molecules coordinated to the metal ion in lanthanide complexes have been profusely investigated during the last 25 years, especially in the case of Gd 3+ and Eu 3+ complexes. This is mainly related to the important application of some Gd 3+ complexes as contrast agents in magnetic resonance imaging (MRI), and the intensive investigation of Eu 3+ complexes as contrast agent candidates providing contrast through the chemical exchange saturation transfer mechanism (CEST). Both applications require a fine tunning of the exchange rate of the coordinated water molecule to yield optimal response. Herein we review the progress made in this field to control water exchange in a rational way through ligand design, providing relationships between the observed trends, the structures of the complexes and the mechanisms responsible for the water exchange reaction.